2023
DOI: 10.3390/rs15092476
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution and Scenario Simulation of Ecosystem Services under the Impact of Land-Use Change in an Arid Inland River Basin in Xinjiang, China

Zulipiya Kulaixi,
Yaning Chen,
Yupeng Li
et al.

Abstract: Ecosystem services (ESs) are crucial for sustainable development, as they impact human well-being. However, changes in land use/land cover (LULC) caused by climate change and social development can negatively affect ESs, particularly in arid river basins. This study focuses on current and future changes in LULC in the Kaxghar River Basin (KRB) in Xinjiang, China, to determine how these changes will affect the region’s ESs. The integrated PLUS-InVEST model was used to investigate the spatiotemporal distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…The differences in ESV between regions are mainly caused by differences in land-use structure, terrain, time scale, and research area scale. Zuripia et al estimated that the ecosystem service value of the Kashgar River Basin showed an upward trend from 2000 to 2020 [58]. The CA-Markov model is also one of the more accurate prediction methods currently available.…”
Section: Ecological Conservation and Development In The Study Areamentioning
confidence: 99%
“…The differences in ESV between regions are mainly caused by differences in land-use structure, terrain, time scale, and research area scale. Zuripia et al estimated that the ecosystem service value of the Kashgar River Basin showed an upward trend from 2000 to 2020 [58]. The CA-Markov model is also one of the more accurate prediction methods currently available.…”
Section: Ecological Conservation and Development In The Study Areamentioning
confidence: 99%
“…Wang R. Y. et al (2023b) used the PLUS and InVEST models to simulate and predict the spatial development pattern of LULC as well as the changes in carbon stocks in the Greater Bay Area in China in 2030 under multiple scenarios. Kulaixi et al (2023) utilized the PLUS-InVEST model to examine the spatiotemporal distribution and changing patterns of carbon storage under multiple scenarios in an Arid Inland River Basin in Xinjiang, China. Cui et al (2023) used the PLUS model to simulate the future four LULC scenarios and the ecosystem carbon storage was assessed by the InVEST model in Guangdong, China.…”
Section: Introductionmentioning
confidence: 99%
“…It finds extensive application in current research on changes in LUC [29,30]. The Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model serves as a tool to explore the impact of ecosystem changes on benefits to human society [31,32]. It is one of the most widely used models in current CS change studies.…”
Section: Introductionmentioning
confidence: 99%